(untitled) (Clinics, 2009)
OBJECTIVES: We developed a prosthesis for open pleurostomy cases where pulmonary decortication is not indicated, or where post-pneumonectomy space infection occurs. The open pleural window procedure not only creates a large hole in the chest wall that is shocking to patients, also results in a permanent deformation of the thorax. prosthesis for open pleurostomy is a self-retained silicone tube that requires the removal of 3 cm of one rib for insertion, and acts as a mature conventional open pleural window. Herein, we report our 13-year experience with this device in the management of different kinds of pleural empyema. METHODS: Forty-four consecutive patients with chronic empyema were treated. The etiology of empyema was diverse: pneumonia, 20; lung resections, 12 (pneumonectomies, 7; lobectomies, 4; non-anatomical, 1); mixed-tuberculous, 6; and mixed-malignant pleural effusion, 6. After debridment of both pleural surfaces, the prosthesis for open pleurostomy was inserted and attached to a small recipient plastic bag. RESULTS: Infection control was achieved in 20/20 (100%) of the parapneumonic empyemas, in 3/4 (75%) of post-lobectomies, in 6/7 (85%) of post-pneumectomies, in 6/6 (100%) of mixed-tuberculous cases, and in 4/6 (83%) of mixed-malignant cases. Lung re-expansion was also successful in 93%, 75%, 33%, and 40% of the groups, respectively CONCLUSIONS: Prosthesis for open pleurostomy insertion is a minimally invasive procedure that can be as effective as conventional open pleural window for management of chronic empyemas. Thus, we propose that the use of prosthesis for open pleurostomy should replace the conventional method.